Enhanced Assessment of Chest Pain and Related Symptoms in the Primary Care Setting Through the Use of a Novel Personalized Medicine Genomic Test: Results From a Prospective Registry Study. (July 2015) - Ladapo, Joseph A.; Lyons, Heather; Yau, May; Rich, Paul; Newton, Dedra; Bruce-Mensah, Kofi; Johnson, Andrea; Zhou, Yunping; Stemkowski, Stephen; Monane, Mark
Novel approaches for assessing patients with chest pain and related symptoms may improve outpatient care. The REGISTRY I study measured the impact of a personalized gene expression score (GES) on subsequent cardiac referral decisions by primary care providers. Of the 342 stable, nonacute patients evaluated, the mean age was 55 years, 53% were female, and mean (SD) GES was 16 (±10) (range = 1-40). Low GES (≤15), indicating a low current likelihood of obstructive coronary artery disease (CAD), was observed in 49% of patients. After clinical covariate adjustment, each 10-point GES decrease was associated with a 14-fold decreased odds of cardiac referral ( P < .0001). Low GES patients had 94% reduced odds of referral relative to elevated GES patients ( P < .0001), with follow-up supporting a favorable safety profile. This genomic-based test demonstrated clinical utility by guiding decision making during assessment of symptomatic patients with suspected obstructive CAD.